2017
DOI: 10.3892/mmr.2017.6343
|View full text |Cite
|
Sign up to set email alerts
|

Islet-1 induces the differentiation of mesenchymal stem cells into cardiomyocyte-like cells through the regulation of Gcn5 and DNMT-1

Abstract: Previous studies from this group demonstrated that insulin gene enhancer binding protein ISL-1 (Islet-1) specifically induces the differentiation of mesenchymal stem cells (MSCs) into cardiomyocyte-like cells through histone acetylation. However, the underlying mechanisms remain unclear. In the present study, the role of the histone acetylation and DNA methylation on the regulatory mechanism of the Islet-1 was further investigated by methylation-specific polymerase chain reaction (PCR), chromatin immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…ISL1 has been shown to play an essential role in heart embryogenesis, and ISL1-positive cells have been demonstrated to be cardiovascular progenitors [ 17 , 18 ]. Although a recent study demonstrated that overexpression of ISL1 in MSCs induced cardiomyocyte differentiation [ 19 ], a prior study conducted by our group obtained different results [ 10 ]. In our previous study, we found that ISL1 overexpression did not affect their ability to differentiate into cardiomyocytes or endotheliocytes.…”
Section: Discussionmentioning
confidence: 96%
“…ISL1 has been shown to play an essential role in heart embryogenesis, and ISL1-positive cells have been demonstrated to be cardiovascular progenitors [ 17 , 18 ]. Although a recent study demonstrated that overexpression of ISL1 in MSCs induced cardiomyocyte differentiation [ 19 ], a prior study conducted by our group obtained different results [ 10 ]. In our previous study, we found that ISL1 overexpression did not affect their ability to differentiate into cardiomyocytes or endotheliocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Though under undifferentiated conditions both MSC types had a comparable expression of cardiac transcription factors GATA-4, Nkx2.5 and ISL-1 genes but after 5-Aza induction, AF-MSC exhibited a significantly higher expression of these transcription factors at gene as well as protein levels. These transcription factors are key regulators of the expression of cardiac structural genes in MSC as well as in other stem cells and promote their differentiation into cardiomyocytes (20,21). Among these, ISL-1 is of particular importance as it is the earliest transcription factor having a crucial role in cardiogenesis during embryonic development and cardiomyocyte differentiation following cardiac injury in adults (22) and we have observed 40% of AF-MSC to express ISL-1.…”
Section: Discussionmentioning
confidence: 87%
“…It is well known that ISL-1 is essential to the proper formation and development of the heart. ISL1-positive cells, isolated from embryonic stem cells (ESCs), induced pluripotent stem cells, bone mesenchymal stem cells and embryonic or postnatal heart tissues, have the potential to give rise to diverse cell types in the cardiovascular system, including cardiomyocytes, smooth muscle cells, endothelial cells and pacemaker cells (33-35). ISL-1-overexpressing cardiomyocytes exhibit higher beating frequencies in mouse ESC-derived regions and Xenopus hearts, which are associated with the upregulation of nodal‑specific genes and the downregulation of genes associated with the working myocardium (26).…”
Section: Discussionmentioning
confidence: 99%